Chromatin remodelling during male gametophyte development. (21st May 2015) - Borg, Michael; Berger, Frédéric
Summary The plant life cycle alternates between a diploid sporophytic phase and haploid gametophytic phase, with the latter giving rise to the gametes. Male gametophyte development encompasses two mitotic divisions that results in a simple three‐celled structure knows as the pollen grain, in which two sperm cells are encased within a larger vegetative cell. Both cell types exhibit a very different type of chromatin organization – highly condensed in sperm cell nuclei and highly diffuse in the vegetative cell. Distinct classes of histone variants have dynamic and differential expression in the two cell lineages of the male gametophyte. Here we review how the dynamics of histone variants are linked to reprogramming of chromatin activities in the male gametophyte, compaction of the sperm cell genome and zygotic transitions post‐fertilization.